2013
DOI: 10.1177/0265407513478378
|View full text |Cite
|
Sign up to set email alerts
|

Friendship networks and interethnic union formation

Abstract: This article examines the effect of composition of friendship networks during early adolescence on the likelihood of entering an interethnic union among the children of immigrants. We analyze the panel data from the Children of Immigrants Longitudinal Study that followed 14-year-olds into their early 20s. We extend previous research by simultaneously examining the effect of the social context and personal networks and by broadening the type of unions under consideration (i.e., dating and cohabiting unions in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Indeed, a strong version of this expectation has been the premise of school desegregation efforts since the 1950s and college diversity policies since the 1970s, both of which have sought to improve race relations by bringing individuals into contact across racial lines. However, van Zantvliet and Kalmijn (2013) found that interethnic friendships did not mediate the effects of social context on the odds of being in an interethnic relationship. Instead interracial networks may have an additive effect, for example, creating variation among individuals in their response to the same demography and cultural attitudes.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Indeed, a strong version of this expectation has been the premise of school desegregation efforts since the 1950s and college diversity policies since the 1970s, both of which have sought to improve race relations by bringing individuals into contact across racial lines. However, van Zantvliet and Kalmijn (2013) found that interethnic friendships did not mediate the effects of social context on the odds of being in an interethnic relationship. Instead interracial networks may have an additive effect, for example, creating variation among individuals in their response to the same demography and cultural attitudes.…”
Section: Introductionmentioning
confidence: 80%
“…Its sample is not restricted to college students on California campuses (Clark-Ibanez and Felmlee 2004; Levin et al 2007) or to immigrant children in gateway cities (van Zantvliet and Kalmijn 2013), thereby including a larger subsample of African Americans. Add Health also collected network data using name generators that identified friends before asking about their individual characteristics (Smith 2002) instead of asking direct questions that are more vulnerable to social desirability bias, such as “How many black friends do you have?” Add Health’s network data are also preferable to those in the Children of Immigrants Longitudinal Study, which narrowly operationalizes friends’ ethnicity using parents’ country of birth (i.e., “In what countries were your friends’ parents born?”) (van Zantvliet and Kalmijn 2013). Add Health’s main limitation is its sample size, which is far smaller than is typical in marriage studies that rely on census data; thus my analysis also lacks the statistical power to examine every possible interracial combination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…an indicator of the degree to which different groups in society accept each other as equals" (p. 459). In support of this notion, Van Zandvliet and Kalmijn (2013) found that having ethnically diverse friendship networks and attending schools with pupils from other ethnic identities positively affected the likelihood of entering in dating, cohabitation, and marriage with members of other ethnic groups. In a particularly illustrative longitudinal study, Levin, Taylor, and Caudle (2007) found that intergroup dating resulted in more positive attitudes at the end of college, underlining the importance of interethnic dating for the integration of minority groups.…”
Section: Introductionmentioning
confidence: 92%
“…Our choice of instrument is influenced by the existing literature which suggests that geographic factors, such as ethnic and religious diversity, could influence friendship network composition. Specifically, existing literature has demonstrated that the choice of friends or partners is conditional on the pool of potential friends, from which an individual can choose (see, e.g., Kalmijn & Flap, 2001;Van Zantvliet & Kalmijn, 2013). Thus, geographic distribution determines the composition of friendship networks, given that opportunities for social contact determine social associations (Blau, 1977;Lieberson & Waters, 1988).…”
Section: Wherementioning
confidence: 99%